2013
DOI: 10.5296/ajfa.v5i2.4039
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Undergraduate Students’ Understanding of Shari’ah Based Audit: Implications for the Future of Shari’ah Auditing Labor Market in Brunei

Abstract: The worldwide Islamic finance industry had grown remarkably in the past decades, primarily propelled by the strong demand for shari'ah (Islamic Law) compliant banking products by Muslims and non-Muslims alike. Behind the façade of such outstanding industry's development, there remain unresolved critical governance issues warranting for immediate attention by industry stakeholders. Besides the presence of significant variations with regards to the scope and framework for shari'ah audit in the currently availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…For example, the Shariah standards of AAOIFI for Islamic products and activities, governance benchmarks of AAOIFI for Shariah compliance and review eISSN: 2395-6518, Vol 7, No 1, 2019, pp The researchers in Brunei are the only ones that have specifically addressed the issues pertaining to Shariah audit among students. They are the first to conduct an exploratory study of Shariah audit to explore the students' awareness and comprehension on Shariah audit's term and concept (Yaacob & Donglah, 2012;Yaacob, Shafeek & Nahar, 2013). It reveals that the students did not have a high level of awareness and comprehension on Shariah audit's term and concept.…”
Section: Important Of Education On Internal Shariah Auditmentioning
confidence: 99%
“…For example, the Shariah standards of AAOIFI for Islamic products and activities, governance benchmarks of AAOIFI for Shariah compliance and review eISSN: 2395-6518, Vol 7, No 1, 2019, pp The researchers in Brunei are the only ones that have specifically addressed the issues pertaining to Shariah audit among students. They are the first to conduct an exploratory study of Shariah audit to explore the students' awareness and comprehension on Shariah audit's term and concept (Yaacob & Donglah, 2012;Yaacob, Shafeek & Nahar, 2013). It reveals that the students did not have a high level of awareness and comprehension on Shariah audit's term and concept.…”
Section: Important Of Education On Internal Shariah Auditmentioning
confidence: 99%
“…In this case, each student who participated in this training program was requested to evaluate their understanding (dependent variable) and knowledge (independent variable) of Shariah audit prior to and after completing the CPSA program. To measure such understanding and knowledge, this study employed a 5-point Likert scale consisting of "(1) = very low" to "(5) = very high" which had been used widely in similar previous studies Khalid et al, 2019;Yaacob & Donglah, 2012;Yaacob et al, 2013). The list of items and respective variables used in this study is listed in Appendix A.…”
Section: Research Methodology Data Collection Processmentioning
confidence: 99%
“…Another similar study was conducted by Yaacob et al (2013) on 59 undergraduate students in Brunei. In this study, they found that 60% of the students were not aware on Shariah auditor roles.…”
Section: Impact Of Shariah Audit Training On Students' Understandingmentioning
confidence: 98%
“…It's worth noting that the study conducted before to the publication of SGF 2011 focused on the idea for a single Shariah compliance component in any IFI. Prior to the issuance of the SGF, the focus of the research is on shariah audit practise, shariah audit human resources, issues and challenges and shariah audit awareness Yaacob et al, 2013;. Mohd Ali & Shafii, 2014;Kassim & Zuraidah, 2013;Ab.…”
Section: Empirical Studies On Shariah Auditmentioning
confidence: 99%